Inovasi Pelayanan Publik â€œSapaku Malamâ€ di Kecamatan Kuta Utara, Kabupaten Badung - Ida Ayu Ratna Kartika Dewi (Universitas Warmadewa, 2020)
Until now, public services in Indonesia in general are still many problems. The need for ideal services has not yet materialized. One of the most important processes in realizing public service improvement is to make an innovation breakthrough. The existence of laws and regulations governing regional innovation becomes a reference for the Regional Government to innovate in order to improve the quality of public services. One of them is the public service innovation â€œSapaku Malamâ€ in Kuta Utara District, Badung Regency. This type of research is qualitative descriptive with data collection techniques through observation, interviews and documentation. This study aims to determine the implementation, driving and inhibiting factors, and the impact of the public service innovation. The results showed that the implementation of the Public Service Innovation